EXPRESSIVE AESTHETIC FEATURES OF TRADITIONAL UKRAINIAN PAINTING AND ITS APPLICATION - Романенко, Наталія; Помиляйко, Юлія (SWorldJournal, 2023)
IntroductionThe popularization of Ukrainian ethnic traditions in the world today has significantly increased as resistance to Russia’s invasion of Ukraine, resistance to the destruction of cultural ethnic heritage, which is most closely related to the Uk